Casting of Fe-(2-12)Mn-(4-14)Al-(0.09-0.7)C low-density steel via artificial slag practice - Keler, Memduh Kagan; Daglilar, Sibel; Kuskonmaz, Nilgun; Cetin, Zafer; Kart, Onur; Gunduz, Oguz; Gunduz, Oguzhan (ELSEVIER, 2022)
In this research theoretical and practical studies have been highlighted about alloy design, casting and steel-slag interaction. The use of a protective slag layer was identified as an advantageous method in the production of low-density steels. For the first time in this study, a unique synthetic steelmaking (CaO/Al2O3:1.57) slag was implemented in an induction furnace with no vacuum chamber to produce high aluminum in steel. This study showed that manganese and aluminum directly influence the solidification structure and carbide formation. Coarser k-carbides have been detected at grain boundaries in austenite as-cast matrix when the Aluminum increases in the low-density steel.
Keywords: Low-density steels; Cast; Artificial slag usage; Induction furnace melting; Solidification; MECHANICAL-PROPERTIES; AL; Materials Science; Physics